Reskilling and Upskilling in The Digital Era: Challenges and Human Resource Management Strategies - Riyanto, Sugeng (International Journal of Sharia Business Management, 2025)
The rapid advancement of digital technologies has drastically reshaped the industrial landscape, compelling the workforce to acquire new competencies to remain relevant and competitive. Within this context, reskilling and upskilling have emerged as critical strategies for organizations in managing human resources (HR) and adapting to accelerated technological change. Nevertheless, the implementation of reskilling and upskilling is fraught with challenges, including widening skill gaps between older and younger employees, resource limitations for training, and resistance to change among workers. This study aims to analyze these challenges and identify effective HR management strategies to address them. A qualitative approach was employed, combining a systematic literature review and secondary data analysis from both academic and industry sources. The findings indicate that technology-enabled strategies, such as e-learning, microlearning, and AI-driven training, are essential to workforce development. Moreover, hybrid learning models, which integrate online and face-to-face training, have been shown to enhance training efficiency. Cross-sector collaboration among corporations, educational institutions, and governments is also highlighted as a key success factor in implementing reskilling and upskilling programs. Practical implications suggest that organizations should embed reskilling and upskilling within HR policies, foster a culture of continuous learning, and allocate sufficient resources to employee training. This study contributes to both theory and practice by providing insights into adaptive and innovative HR development strategies in the digital era. Future research is recommended to further investigate the impact of reskilling initiatives on employee productivity and performance.